2012
DOI: 10.1186/1743-422x-9-33
|View full text |Cite
|
Sign up to set email alerts
|

Application and removal of polyanionic microbicide compounds enhances subsequent infection by HIV-1

Abstract: BackgroundContinued efforts are being directed toward the development of microbicides that will be used to reduce or eliminate the risk of HIV-1 sexual transmission. Unfortunately, clinical trials involving polyanion-containing microbicide formulations, including Carraguard (λ-carrageenan [LC]) and Ushercell (cellulose sulfate [CS]) demonstrated that these products were ineffective and may have, in some circumstances, increased the risk of HIV-1 infection. These findings prompted reassessments of the in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…Moreover, knowing that a vaginal gel does not exacerbate rectal infection is important. Despite in vitro data suggesting a potential enhancing effect of CG on HIV infection, 4,24,25 we have found no evidence of CG-mediated enhancement in macaques following vaginal or rectal application, even when challenging up to 24 h after gel dosing (data herein and unpublished observations). 4,10,11,26 This also supports the earlier findings from the Phase 3 trial testing the efficacy of CG against HIV infection, where the HIV infection frequency was reduced, albeit not significantly, in the CG arm 27 and that HIV shedding was not enhanced in HIVinfected women using CG.…”
Section: Discussionmentioning
confidence: 47%
“…Moreover, knowing that a vaginal gel does not exacerbate rectal infection is important. Despite in vitro data suggesting a potential enhancing effect of CG on HIV infection, 4,24,25 we have found no evidence of CG-mediated enhancement in macaques following vaginal or rectal application, even when challenging up to 24 h after gel dosing (data herein and unpublished observations). 4,10,11,26 This also supports the earlier findings from the Phase 3 trial testing the efficacy of CG against HIV infection, where the HIV infection frequency was reduced, albeit not significantly, in the CG arm 27 and that HIV shedding was not enhanced in HIVinfected women using CG.…”
Section: Discussionmentioning
confidence: 47%
“…As a vaginal or rectal microbicide may not be toxic nor stimulate HIV target cells, we showed that LA did not activate PBMCs, nor increased their susceptibility for HIV-1 infection as our control agents tenofovir, PRO2000 or acyclovir ( Fig 7 ). In contrast, application and removal of cellulose sulfate and carrageenan, resulted in an enhanced subsequent HIV-1 infection in vitro [ 70 ]. Further studies pointed out that cellulose sulfate altered the epithelial architecture by affecting junctional proteins (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…VivaGel has shown anti-SHIV activity when applied only 20 min before challenge with 2,500 TCID 50 SHIV 89.6P (60), and the anti-HSV-2 window of protection shows 75% to 88% protection when applied up to 30 min before and 27% protection when applied 1 h before HSV-2 at 10 4 PFU (63). VivaGel is also claimed to exhibit anti-HPV activity, but there are no published reports available to compare its activity with the strong in vitro and in vivo anti-HPV activity of carrageenan (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…CG represents an excellent delivery vehicle for ZA. It has been shown to be safe and acceptable in numerous preclinical and clinical studies (7,19,22,(25)(26)(27)(28)(29)(30)(31)(32) despite contradictory observations using in vitro systems that CG can enhance HIV infection (22,33). Additionally, CG may have activity against HPV (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%